The nexus between tourist motivation and satisfaction in lekki urban forest and animal shelter initiative (LUFASI) Lagos state, (Nigeria) - Olubukola Mary Ogundare; Adekunle Olufemi Oloyede; Olakunle Shakur Olawuyi; Morayo Phebe Abimbola (Zbornik radova Departmana za geografiju, turizam i hotelijerstvo)
Tourism refers to the act of individuals or groups spending time away from home for amusement, relaxation, and pleasure while utilizing commercial services. Meanwhile, the patronage of tourist destinations in Nigeria is influenced by various factors, including motivations and perceptions visitors had when they visit such destinations, which can impact customer patronage. This study was carried out in LUFASI in Lagos state, Nigeria. A total number of 359 respondents were selected using Yamane (1967) formula. A well-structured close-ended questionnaire was used for data collection, and the results were statistically analyzed using both descriptive and inferential statistics. This study revealed that the primary motivation for most respondents to engage in tourism was fun, with 49.9% of the respondents agreeing and 44.3% strongly agreeing. Additionally, 45.4% were satisfied and 44.0% of the respondents were very satisfied with the park. The visitors were motivated to visit the park for the following reasons: novelty, relaxation/escape, relationships, nature, and self-development. The study also found that the management of LUFASI Park is doing a commendable job in managing and protecting their natural environment by ensuring that the inflow of tourists and their activities does not af fect the natural resources. Lufasi Park has an impressive environment that provides a high level of satisfaction for tourists from diverse backgrounds.